Strategic planning for parasite control on livestock farms. (2nd March 2019) - Forbes, Andrew
Abstract : There are several approaches to the control of parasites in sheep and cattle, ranging from therapeutic, when actions are only taken when clinical disease is observed, to strategic, when steps are taken to anticipate and mitigate the risk of disease and production losses. Strategic programmes generally result in high levels of animal welfare through the avoidance of clinical disease and superior animal performance by reducing exposure to pathogens. Implementation of strategic actions requires forward planning and may not be straightforward in some systems, for example, all-year-round calving dairy herds. The main tools for strategic control are pasture management, nutrition, vaccination and medication; general principles and examples are provided in this article.